SEXUAL AND REPRODUCTIVE HEALTH OF YOUNG PEOPLE RESIDENTS IN A DISTRICT OF LIMA - Aspilcueta, Daniel (2015)
OBJECTIVES: To determine Comas district youngsters both sexual and reproductive health conditions. DESIGN: Descriptive, exploratory and transversal study. MATERIALS AND METHODS: In 2002, 92 Comas district 15 to 24 year-old youngsters were interviewed by a semi-structured questionnaire. RESULTS: Half of the youngsters having sexual relations used some type of contraception, having received information mainly from their teachers and the family; 75% of the youngsters did not attend a health establishment, but 11% had a Papanicolaou smear and 9% attended a general medicine service. CONCLUSION: The sexual and reproductive health conditions of the youngsters studied were acceptable.